Cumplimiento de Buenas Prácticas de Dispensación en un establecimiento de oficina farmacéutica privado, Chimbote 2022 - Palma Lucio, Josselin Estefania (2023)
The purpose of this article is to determine compliance with good dispensing practices in a private pharmacy in the city of Chimbote in the year 2022, for which it was prepared from March to May 2022, with the following results. The percentage distribution of compliance with the "Acceptance and Approval of the Requirement" allows evaluating that the evaluated personnel reached 100% compliance in March and that in May they had the same percentage of compliance with the "Analysis and Interpretation of the Requirement in March it was only 100% 75%, in May it was 100%. In the area of "production and selection for product delivery" we estimate staff compliance at 83.3% for March and 100% for May. With a "record" of, we can judge that the evaluated employees fully comply with the legislation. In the "Provision of products and information" area, 100% was achieved in the months evaluated. In summary, compliance with good distribution practices at the Farma Primavera Chimbote pharmacy was 95.3% from the end of March to May 2022, always seeking the perfect distribution